2012
DOI: 10.1186/1477-7819-10-224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of muc4 expression in gallbladder carcinoma

Abstract: BackgroundMucins are high molecular glycoproteins and play protective and lubricating roles in various epithelial tissues. Deregulated expression of mucins is involved in carcinogenesis and tumor invasion. MUC4 expression has been identified as a poor prognostic factor in pancreatobiliary carcinomas. To date, the relation between MUC4 expression and prognosis in gallbladder carcinoma remains to be determined. Authors examined MUC4 expression in gallbladder carcinoma and investigated its impact on prognosis.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The survival analysis showed that MUC-4 expression was statistically significant risk factors affecting the outcome of the patients with intrahepatic cholangiocarcinoma-mass forming type as an independent risk factor (Shibahara et al, 2004). MUC 4-positive patients had a definite trend towards better survival of laryngeal squamous cancer (Paleri et al, 2004) and gallbladder carcinoma (Lee et al 2012). In addition, patients with MUC-5AC-positive tumors also had poor clinicopathological parameters and showed shorter survival than those with MUC-5AC-negative gastric cancer (Kocer et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…The survival analysis showed that MUC-4 expression was statistically significant risk factors affecting the outcome of the patients with intrahepatic cholangiocarcinoma-mass forming type as an independent risk factor (Shibahara et al, 2004). MUC 4-positive patients had a definite trend towards better survival of laryngeal squamous cancer (Paleri et al, 2004) and gallbladder carcinoma (Lee et al 2012). In addition, patients with MUC-5AC-positive tumors also had poor clinicopathological parameters and showed shorter survival than those with MUC-5AC-negative gastric cancer (Kocer et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Although several clinicopathologic features have been the standard for determining the clinical outcome of GBC patients, this classification scheme is probably an imprecise predictor of the prognosis of an individual patient [22]. Thus, it is necessary to identify novel and effective biologic markers which are associated with advanced tumor progression for the early diagnosis and the discovery of a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is crucial to investigate mucin/s which is more prominently present in stone bearing gallbladder tissue than without stone. There are many studies which shows presence of different mucins in gallbladder tissue like MUC1 [23], MUC2 [24], MUC4 [25], MUC5AC [26], MUC5B [27], MUC6 [28] etc. So we decided to see all secretary/ gellforming mucins in stone bearing gallbladder tissue.…”
Section: Discussionmentioning
confidence: 99%